2011
DOI: 10.1121/1.3635298
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-cardioid directivity on incidence angle estimation using the polar energy time curve

Abstract: Assessment of desirable reflections and control of undesirable reflections in rooms are best accomplished if the reflecting surfaces are properly localized. Several measurement techniques exist to identify the incident direction of reflected sound, including the useful polar energy time curve (Polar ETC), which requires six cardioid impulse response measurements along the Cartesian axes. The purpose of this investigation is to quantify the incidence angle estimation error introduced into the Polar ETC by non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…where^represents a Hilbert transform operator. 26,27 eðtÞ may be smoothed (for each time sample, the sample and neighboring samples may be averaged). The inverse of the envelope is calculated and multiplied once by the original TRIR signal to obtain the decay compensation signal, dcðtÞ, dc t ð Þ ¼ 1 e t ð Þ ir Àt ð Þ:…”
Section: Decay Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…where^represents a Hilbert transform operator. 26,27 eðtÞ may be smoothed (for each time sample, the sample and neighboring samples may be averaged). The inverse of the envelope is calculated and multiplied once by the original TRIR signal to obtain the decay compensation signal, dcðtÞ, dc t ð Þ ¼ 1 e t ð Þ ir Àt ð Þ:…”
Section: Decay Compensationmentioning
confidence: 99%
“…This room is chosen because the hard wall reflections, and therefore long reverberation time, contribute to a high amplitude focus as shown by Ribay et al 17 The measured reverberation time for the room was found to be 6.89 s and the Schroeder frequency of the room was determined to be 385 Hz. 27 All experiments are performed at frequencies above the Schroeder frequency to ensure a diffuse sound field in the chamber.…”
Section: A Experimental Setupmentioning
confidence: 99%